Abelhas das orquídeas (Apidae: Euglossini) e as plantações de palma de óleo (Elaeis guineensis Jacq.) na Amazônia Oriental: mudanças na composição de espécies, tamanho corporal e diversidade funcional - BRITO, Thaline de Freitas (Universidade Federal do Pará, 2019)
In this study, we evaluated the role of legal reserves (LR) and areas of permanent protection (APP) in the maintenance of orchid bee species, and we tested the influence of abiotic and habitat parameters on taxonomic and functional diversity of this group. In addition, we investigated the occurrence of phenotypic variations (body and wing size, and fluctuating asymmetry) in response to environmental stress caused by oil palm plantations. Orchid bee males were sampled in nine areas (3 RL, 3 APP, and 3 oil palm plantations) in the municipality of Tailândia, southeast of the state of Pará. In each area, we installed six separate sampling stations, 500 m apart, each one with six scent traps; totaling 36 traps per area, and 108 per habitat type. We compared differences in observed abundance and richness using a One-Way ANOVA, we evaluated species composition patterns with a PCoA, and we also used a species indicator analysis. A partial RDA was applied to evaluate the influence of habitat attributes, space and habitat type on taxonomic and functional parameters of bees. In addition, we compared body and wing size variations of the individuals through the types of habitat. Our results indicate that oil palm areas are characterized by the presence of few individuals and species, low functional diversity, and by larger bees. Despite this, we recorded four species associated to LR, which can be useful indicators of orchid bee’s communities in the Amazon rainforest. The habitat structure was not a good predictor of both functional and taxonomic composition, and no levels of fluctuating asymmetry were detected, but bees from oil palm showed larger wings compared to forest areas. Our research highlights that APPs play an important role in maintaining both taxonomic and functional composition of orchid bees, which could reinforce the fact that bees use these areas as displacement corridors in a matrix formed by oil palm plantation. Thus, both LRs and PPAs areas fulfill their purpose of protecting the biodiversity of orchid bees.